Effect of hydrogenation on the optical and structural properties of GaAs thin films prepared by rf-magnetron sputtering - Azevedo, G. D.; Da Silva, JHD; Avendano, E. (Elsevier B.V., 2005)
We have utilized infra-red and optical absorption measurements, grazing incidence X-ray diffraction (GIXRD) and extended X-ray absorption fine structure (EXAFS) measurements to investigate the influence of hydrogenation on the optical and structural properties of GaAs thin films prepared by rf-magnetron sputtering. Hydrogenation induces distinct changes in the optical properties, namely shifts in the absorption edges and reduction of the Urbach energy. Such modifications are correlated to a reduction in structural disorder as determined by EXAFS and the increase of crystallinity determined by GIXRD. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: EXAFS; gallium arsenide; GaAs; sputtering; hydrogenation